Influence of Monitoring and Evaluation System on the Performance of Projects - Okafor, Afomachukwu (IJRDO - Journal of Social Science and Humanities Research, 2021)
Monitoring and Evaluation (M&E) is a project management function. It is also a part of the project cycle, which aids the tracking of the project performance at any given time, as well as provides reasons for any observed project status. The monitoring and evaluation system is made up of components that make it functional. A well developed monitoring and evaluation plan, the skills for M&E and M&E information management systems are vital components of the Monitoring and Evaluation system that influences the performance of a project but this has been because an M&E system has been seen by organizations as a donor requirement rather than a management tool. The broad objective of the study was to assess the influence of the monitoring and evaluation system on the performance of the Reading and Numeracy Activities (RANA) Project in Katsina State of Nigeria. The specific objectives were to assess how monitoring and evaluation plans, monitoring and evaluation skills and M&E Information Management systems influence the performance of the RANA project. The study was guided by the theory of change and the realistic evaluation theory. The study adopted a descriptive survey research design and targeted all the 32 employees working on the RANA Project because of the limited number of employees. Data was collected through questionnaires and interview guides, which were pilot-tested before use and utilized the Cronbach alpha test on SPSS to measure both reliability of the research tool and the internal consistency. The data was analyzed using descriptive statistics which includes correlation analysis aided by Statistical Package for Social Science for quantitative while the qualitative data was analyzed using narrative and thematic methods. Results showed that monitoring and evaluation indeed has an influence on project performance as a management function. This is demonstrated in activities like M&E plan which comprised of appropriate performance indicators for measuring performance, data collection schedules and methods of data analysis well developed prior to project implementation. By this all the appropriate measures to ensure project performance is enhanced, are well taken care of. The results further showed that 94% of the respondents had the skills for M&E. 100% were acquainted with the M&E plan for the project and confirmed the existence of a system for data capturing for the project noting that all data collection from baseline surveys, progress monitoring data, etc. were all captured in the project database. On average, 94% of the respondents gave credible reasons why they thought that M&E influences project performance in reference to the project under study. Spearman’s correlation showed a positive relationship of 0.64 between M&E and project performance. Particularly, it showed that M&E plan had an approximate correlation coefficient of 0.8 and M&E skills and M&E Information management system also showed a statistically significant correlation with project performance at 0.698 and 0.474 respectively. In conclusion, the study showed a directly proportional influence of project performance by monitoring and evaluation. It also showed that for a visible positive influence on project performance to be seen, an M&E plan should be in place. Similarly, M&E is to be systematically implemented in full in order for it to influence project performance. The study therefore recommends the institutionalization of M&E in organizations by ensuring an existence of an M&E unit with adequate staffing owing to the critical influence of M&E on project performance.